La tercera virgen - Vargas, Fred; Suárez Girard, Anne-Hélène; Vargas, Fred. (Madrid : Siruela, 2012)
On the outskirts of Paris, two men have been found with their throats cut, and despite the common assumption that the crime is a drug-related incident, Commissaire Adamsberg becomes convinced that the deaths are the work of a serial killer with split personalities and enlists the assistance of pathologist Ariane Lagarde to help him unravel the truth.
Online resource; title from ePub title page (Digitalia, viewed April 15, 2016)
Keywords: Adamsberg, Jean-Baptiste -- (Fictitious character) -- Fiction; Police -- France -- Paris -- Fiction; Murder -- Investigation -- France -- Paris -- Fiction; Paris (France) -- Fiction; Noir fiction; Detective and mystery fiction; Electronic books